1961
DOI: 10.1038/icb.1961.14
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Secretion of Nitrogen in Sheep Saliva

Abstract: SUMMARY.Differential responses occurred in the amount of urea nitrogen and total nitrogtsn secreted in the parotid saliva, according to the nitrogen status of the sheep, when 1-4 gm. of urea nitrogen was injected into the hlood daily. Of this amount of nitrogen, 01 gm. could be recovered in the secretion from one parotid gland daily when the sheep were in positive nitrogen balance, and 0-3 gm. when the sheep were in negative nitrogen balance.The urinary excretion accounted for 1-0 gm. of the 1-4 gm. of urea ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1964
1964
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…In sheep given lucerne hay or pellets, the transfer of approximately 1-3 g N/d is probably maintained by salivary secretion of urea (Nolan & Leng, 1972). In sheep given brome grass pellets, salivary secretion attains 5-7 l/d (Kennedy & Milligan, 1978b) which would contribute 0.4-0.6 g urea-N/d, assuming a concentration of plasma urea of 140-150 mg N/1 and that salivary urea concentration was 0.6 that of plasma urea (Somers, 1961). Therefore transport of urea across the rumen epithelium may contribute up to 9 g N/d, or approximately 0.9 of the total transfer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In sheep given lucerne hay or pellets, the transfer of approximately 1-3 g N/d is probably maintained by salivary secretion of urea (Nolan & Leng, 1972). In sheep given brome grass pellets, salivary secretion attains 5-7 l/d (Kennedy & Milligan, 1978b) which would contribute 0.4-0.6 g urea-N/d, assuming a concentration of plasma urea of 140-150 mg N/1 and that salivary urea concentration was 0.6 that of plasma urea (Somers, 1961). Therefore transport of urea across the rumen epithelium may contribute up to 9 g N/d, or approximately 0.9 of the total transfer.…”
Section: Discussionmentioning
confidence: 99%
“…Weston & Hogan (1967) suggested a maximal transfer of blood urea to the rumen of sheep of approximately 5 g N/d, while Nolan & Leng (1972) concluded that only 1.2 g N/d was transferred in sheep given lucerne (Medicago sativa) hay. Secretion of urea in saliva contributes to the transfer of blood urea to the rumen (Somers, 1961), but Houpt (1959) estimated that transport of urea across the rumen epithelium could account for up to 0-95 of the total transfer. Nolan & Leng (1972) suggested, however, that in their study virtually all the transfer occurred by way of saliva.…”
mentioning
confidence: 99%
“…The studies of Somers (1961b) indicate that secretion of nitrogen in saliva has an upper limit; this work showed that following a single intracarotid infusion of urea, the secretion of total nitrogen or urea in parotid saliva reached an upper limit when blood urea nitrogen level was approximately 30 mg/100 ml and did not increase with further increase in blood urea concentration. It is possible that a similar limitation to salivary nitrogen secretion existed in the present studies but at a lower blood urea concentration.…”
Section: (E) Transfer To the Rumen Of Nitrogen Infused Per Abomasummentioning
confidence: 98%
“…A large proportion of the salivary nitrogen is urea (Bailey and Balch 1961;Somers 1961a) while Ash and Dobson (1963) have shown that urea is one of the nitrogenous substances entering the rumen through the rumen wall.…”
Section: Introductionmentioning
confidence: 99%
“…Transfer of blood urea-N to the rumen Assuming salivary urea-N concentration is 0.60 of that in blood (Bailey & Balch, 1961 ;Somers, 1961) and total salivary flow was 11 litres/d (average reported by Kay (1960)), contributions of salivary urea-N to the rumen were estimated as 0.3 (diet A), 0.6 (diet B) and 1.0 (diet C) g N/d. Although these are only approximations, it would appear that all blood urea-N transferred to the rumen cannot be accounted for by saliva alone, since these values represent only 8, 13 and 38% of the total transfer measured (diets A, B and C respectively).…”
Section: Enrichments Of Microbial-n and Abomasal Nh-nmentioning
confidence: 99%